The Impact of Green Accounting, Carbon Emission Disclosure, and Environmental Performance on Mining Companies’ Valuation - Surianti, Meily; Sibarani, Angie Gracia; Sibarani, Jojor Lisbet; Ginarti, Cahyo; Gultom, Selfi Afriani (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
This examines and evaluates how green accounting, carbon emission disclosure, and environmental performance affect the valuation of mining companies that are listed on the IDX. agency administrations contribute to growing the employer's esteem, which causes herbal harm because of the enterprise's types of trade. Auxiliary data from mining organizations' annual reports and preservation reports, along with related environmental and forest carrier tests for the years 2021–2023 are the sources of information used in this observation. The research strategy used a purposive check, so that forty-five perceptual information had been obtained from 15 companies. The look at become carried out the use of a multivariate actual research with the SEM-PLS approach and the assist of the clever-PLS software. The study's findings indicate that while carbon emissions have a high-quality impact on goodwill, herbal execution has a fantastic impact on goodwill, and green accounting has a negative effect.